(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
The study was conducted in 2025, and aimed to estimate the compositional and structural diversity in some parks of Tartous City. Fifteen parks were chosen. All trees and shrubs in these parks were inventoried. The sustainability of these parks was evaluated using multiple biodiversity indicators. The results indicated that all parks exceeded the 10/20/30 rule, except four of them that met the rule at the family level. The diversity according to the diameter classes was good in only 20% of the parks. 67 plant species of trees and shrubs were recorded in the studied parks, belonging to 57 genera and 32 plant families. The study found a statistically significant correlation between the park area and both species richness (R=0.87, P<0.001) and Shannon’s index (R=0.68, P=0.005), while no statistically significant correlation was found between area and the top diversity index (TD-50) (R=0.42, P=0.12). Hibiscus × rosa-sinensis was the most abundant species, accounting for 21.78% of the total, with Cascabela thevetia being next at 11.61%, Ficus nitida at 11.47%. Ficus nitida was among the three dominant species in 60% of the gardens, followed by Casuarina cunninghamiana in 40% of them. The Malvaceae family was the most abundant, followed by Apocynaceae and Moraceae. The percentage of introduced species was 68.65%, making them the preferred species. The study. provides a database that can be used to manage parks optimally, ensuring their sustainability and the provision of their services. It also recommends utilizing local species in creating green spaces in the city based on scientific principles